Design and analysis of chassis jig for formula student electric vehicle (Nanyang Venture Formula) - Lim, Coral Chu Yu (Nanyang Technological University, 2021)
The purpose of this Final Year Project was to research, analyse and fabricate the chassis in coordination with other subcomponents of a vehicle meant to compete in Formula Society of Automotive Engineers (FSAE) in their Japan race slated for July 2022. As this is Nanyang Technological University’s (NTU’s) virgin entry at FSAE, the team at Nanyang Venture Formula is aiming at passing the technical inspection of the competition, which usually disqualifies 60% of participating teams. This implies strict adherence to the rules of the competition.